Can laparoscopic nerve-sparing ultra-radical hysterectomy play a role in locally advanced cervical cancer? A single-center retrospective study - Wei, Wei-wei; Zheng, Hong; Shao, Panqiu; Chen, Xia; Min, Yi-fei; Tang, Bin; Sun, Hui-ting; Chen, Ji-ming; Shi, Ru-xia (Frontiers in Oncology, 2022)
Background and objectives The objective of this study is to investigate the outcomes of concurrent platinum-based chemoradiation therapy (CCRT), laparoscopic nerve-sparing ultra-radical hysterectomy (LNSURH), and open radical hysterectomy (ORH) on patients with locally advanced cervical carcinoma (LACC). Methods A single-center retrospective study was conducted on LACC patients who received CCRT, ORH, or LNSURH from January 2011 to December 2019. Data on age, tumor size, overall survival (OS), disease-free survival (DFS), and early and late morbidities were collected. After 24 months of treatment, patients were asked a series of questions about their urinary, bowel, and sexual activities. Early morbidities were defined as those occurring during or within a month of treatment, whereas late morbidities and complications were defined as those occurring a month after treatment. The postoperative complications were classified with reference to the Clavien–Dindo classification (CD) system. Results The Kaplan–Meier curves revealed no significant differences in OS and DFS among the three groups (P = 0.106 for DFS and P = 0.190 for OS). The rates of early complications in the CCRT group were comparable with those in the operated groups (P = 0.46). However, late complications were significantly lower in the ORH and LNSURH groups relative to those in the CCRT group. The scores of urinary and bowel functions were restored to the pretreatment state, although the sexual function scores were not satisfactory. Conclusions The treatments of CCRT, ORH, and LNSURH can be considered options for patients with LACC, as their OS and DFS showed no significant difference. In addition, LNSURH exhibited a lower incidence of late complications and high sexual function scores.